2021
DOI: 10.3390/min11090998
|View full text |Cite
|
Sign up to set email alerts
|

Acid Mine Drainage Sources and Impact on Groundwater at the Osarizawa Mine, Japan

Abstract: Understanding the origin of acid mine drainage (AMD) in a closed mine and groundwater flow system around the mine aids in developing strategies for environmental protection and management. AMD has been continuously collected and neutralized at Osarizawa Mine, Akita Prefecture, Japan, since the mine was closed in the 1970s, to protect surrounding river water and groundwater quality. Thus, water samples were taken at the mine and surrounding groundwaters and rivers to characterize the chemical properties and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…A recent study reported groundwater pollution in the Osarizawa Mine area, Akita Prefecture, Japan. Although mining activities have stopped since the 1970s, the impact on groundwater quality degradation is still happening (Nishimoto et al, 2021) . Using contaminated groundwater for bathing and drinking will cause various health problems.…”
Section: Impact Of Amd On the Environmentmentioning
confidence: 99%
“…A recent study reported groundwater pollution in the Osarizawa Mine area, Akita Prefecture, Japan. Although mining activities have stopped since the 1970s, the impact on groundwater quality degradation is still happening (Nishimoto et al, 2021) . Using contaminated groundwater for bathing and drinking will cause various health problems.…”
Section: Impact Of Amd On the Environmentmentioning
confidence: 99%
“…Actions to prevent the formation of AMD have been attempted, one of which is the application of encapsulation. However, the formation of AMD cannot be avoided, so efforts need to be made to treat AMD in various forms, both through active and passive processing (Nishimoto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…AMD derived from closed coal mines (CCMs) presents a substantial pollution risk to the whole WRB. It has been widely reported that AMD could induce serious water pollution and damage to aquatic ecosystems in river and groundwater globally [ [4] , [5] , [6] , [7] , [8] ]. Therefore, a comprehensive understanding of the hydrochemistry of AMD derived from CCMs is particularly important for environmental pollution prevention and ecological protection in the WRB.…”
Section: Introductionmentioning
confidence: 99%